WebGIS and land planning data management: a study of Hanoi University of Civil Engineering’s Campus 2 - Luong, Ngoc Dung; Duong, Cong Hieu (Geodesy and Cartography, 2025)
The use of WebGIS in urban land planning and management has become a global trend. A Web-GIS system was developed specifically for planning management at HUCE’s Campus 2. While not yet fully complete, the findings indicate that this system has provided substantial support to stakeholders, including local authorities, planners, and the broader community. Through efficient data management and analysis, the WebGIS system has facilitated timely monitoring and adjustments during the construction process, while also enabling comprehensive modifications to land planning. Additionally, its field interaction function gathers valuable information for detecting damages requiring repair and maintenance, along with updates on the status of areas where land use rights have not yet been transferred. Despite certain limitations, such as challenges in integrating 3D model data and enhancing public consultation methods, the incorporation of these research findings offers significant potential to improve the effectiveness of urban land planning and management in the future.